Kinerja Birokrasi Pelayanan Pencatatan Akte Perkawinan pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pulau Morotai Tahun 2017 - Sri Ka’bah (Jurnal Ilmiah Wahana Pendidikan, 2019)
This research was conducted based on the basis of criticism aimed at the Department of Population and Civil Registration of the Island of Morotai Regency which in serving the community is not too professional and also increasingly requires certainty of time, the number of convoluted procedures. In the service of marriage certificate registration at the Department of Population and Civil Registration, Morotai Island Regency prioritizes the management of marriage certificates that are still related to the quality of services provided. The main thing that residents often complain about is the problem of very long service times. This research method is qualitative naturalistic. Public Service Quality, Organizational Structure, Service System. waiting time with waiting time in providing services to the community. There is no computerized system online with related representatives. Determine administrative requirements, Organizational Structure that has not yet determined good conditions. In carrying out their duties, there is an unharmonious relationship between superiors and subordinates. The level of education is good, because everything has enjoyed the world of education